VegPáramo, a flora and vegetation database for the Andean páramo - Cabrera Cisneros, H. (2015)
The páramo region in the northern Andes is very biodiverse, presents high endemism and provides many ecosystem services. Unfortunately, the páramo is critically threatened by anthropogenic activities and climate change. Further research and development of efficient conservation strategies are therefore needed for the region, but they are often limited by the lack of consistent biological data-sources. Here we present Veg- Páramo (GIVD ID: SA-00-002, http://www.givd.info/ID/SA-00-002), a flora and vegetation database for the páramo based on phytosociological vegetation plots. VegPáramo contains data from 3,000 georeferenced vegetation plots with updated nomenclature. The database is accessible through the webportal http://www. vegparamo.com, from which floristic and vegetation data can be freely consulted and downloaded. This new tool should make future botanical and ecological páramo studies easier. VegPáramo is already geographically and floristically representative for the páramo region, but we hope it will continue to grow in scientific significance via new data addition and revision